Peripheral T cell lymphoma, not otherwise specified (PTCL‐NOS). A new prognostic model developed by the International T cell Project Network. (19th April 2018) - Federico, Massimo; Bellei, Monica; Marcheselli, Luigi; Schwartz, Marc; Manni, Martina; Tarantino, Vittoria; Pileri, Stefano; Ko, Young‐Hyeh; Cabrera, Maria E.; Horwitz, Steven; Kim, Won S.; Shustov, Andrei; et al.
Summary: Different models to investigate the prognosis of peripheral T cell lymphoma not otherwise specified (PTCL‐NOS) have been developed by means of retrospective analyses. Here we report on a new model designed on data from the prospective T Cell Project. Twelve covariates collected by the T Cell Project were analysed and a new model (T cell score), based on four covariates (serum albumin, performance status, stage and absolute neutrophil count) that maintained their prognostic value in multiple Cox proportional hazards regression analysis was proposed. Among patients registered in the T Cell Project, 311 PTCL‐NOS were retained for study. At a median follow‐up of 46 months, the median overall survival (OS) and progression‐free survival (PFS) was 20 and 10 months, respectively. Three groups were identified at low risk (LR, 48 patients, 15%, score 0), intermediate risk (IR, 189 patients, 61%, score 1–2), and high risk (HiR, 74 patients, 24%, score 3–4), having a 3‐year OS of 76% [95% confidence interval 61–88], 43% [35–51], and 11% [4–21], respectively ( P < 0·001). Comparing the performance of the T cell score on OS to that of each of the previously developed models, it emerged that the new score had the best discriminant power. The new T cell score, based on clinical variables, identifies a group with very unfavourable outcomes.